Optimisation of culture conditions for a producer clone coexpressing arylsulfatase B and a formylglycine-generating enzyme in order to increase the yield of arylsulfatase B - S. S. Timonova; K. A. Smolova; I. A. Kirik; M. S. Pantyushenko; R. L. Anisimov; R. A. Khamitov; A. A. Piskunov; V. N. Bade (Биопрепараты: Профилактика, диагностика, лечение, 2022)
Maroteaux—Lamy syndrome (mucopolysaccharidosis type VI) is an orphan genetic disease caused by mutations in the arylsulfatase B gene (ARSB), which encodes the lysosomal enzyme arylsulfatase B (ASB). The relevance of the study lies in the need of a Russian recombinant ASB product for patients with the disease in the Russian Federation. Previously, the authors have developed producer lines coexpressing the target ASB enzyme with an auxiliary formylglycine-generating enzyme (FGE), based on Chinese hamster ovary (CHO) cells. Further development of the recombinant ASB preparation places priority on increasing the enzyme yield. The aim of this study was to increase the productivity of producer clones by optimising the culture process and adding calcium chloride and copper sulfate to the culture medium. Materials and methods: a suspension-adapted CHO cell line was used. Monoclonal cell lines were developed using Cell Metric and ClonePix FL systems. The concentration of ASB in the culture liquid was determined using the enzyme-linked immunosorbent assay (ELISA). The authors analysed batch culture and/or fed-batch culture in media supplemented with various concentrations of copper sulfate and calcium chloride. Results: the combined addition of copper sulfate and calcium chloride at concentrations of 300 μM during batch culture of producer clones coexpressing ASB and FGE increases viability and specific productivity of the cells up to 4.58±1.62 pg/ (cell×day). The cultivation of the lead producer clone coexpressing ASB and FGE under fed-batch conditions for 12 days and the addition of copper sulfate to the growth medium at the concentration of 300 μM allow for increasing the yield of the active lysosomal enzyme, arylsulfatase B, to 420 mg/L. Conclusions: the cultivation of producer clones coexpressing ASB and FGE under fed-batch conditions with copper sulfate added to the medium significantly improves cell line growth properties and the ASB yield. This approach to the selection of culture conditions for producer cell lines can be applied to other enzymes of the sulfatase family.